Plasma and Platelet Transfusion Strategies in Critically Ill Children Following Noncardiac Surgery and Critically Ill Children Undergoing Invasive Procedures Outside the Operating Room: From the Transfusion and Anemia EXpertise Initiative–Control/Avoidance of Bleeding. (January 2022) - Tucci, Marisa; Crighton, Gemma; Goobie, Susan M.; Russell, Robert T.; Parker, Robert I.; Haas, Thorsten; Nellis, Marianne E.; Vogel, Adam M.; Lacroix, Jacques; Stricker, Paul A.
Abstract : Objectives: To present consensus statements and supporting literature for plasma and platelet transfusions in critically ill children following noncardiac surgery and critically ill children undergoing invasive procedures outside the operating room from the Transfusion and Anemia EXpertise Initiative - Control/Avoidance of Bleeding. Design: Systematic review and consensus conference of international, multidisciplinary experts in platelet and plasma transfusion management of critically ill children. Setting: Not applicable. Patients: Critically ill children undergoing invasive procedures outside of the operating room or noncardiac surgery. Interventions: None Measurements and Main Results: A panel of 10 experts developed evidence-based and, when evidence was insufficient, expert-based statements for plasma and platelet transfusions in critically ill children following noncardiac surgery or undergoing invasive procedures outside of the operating room. These statements were reviewed and ratified by the 29 Transfusion and Anemia EXpertise Initiative–Control/Avoidance of Bleeding experts. A systematic review was conducted using MEDLINE, EMBASE, and Cochrane Library databases, from inception to December 2020. Consensus was obtained using the Research and Development/University of California, Los Angeles Appropriateness Method. Results were summarized using the Grading of Recommendations Assessment, Development, and Evaluation method. We developed eight expert consensus statements focused on the critically ill child following noncardiac surgery and 10 expert consensus statements on the critically ill child undergoing invasive procedures outside the operating room. Conclusions: Evidence regarding plasma and platelet transfusion in critically ill children in this area is very limited. The Transfusion and Anemia EXpertise Initiative–Control/Avoidance of Bleeding Consensus Conference developed 18 pediatric specific consensus statements regarding plasma and platelet transfusion management in these critically ill pediatric populations. Abstract : Supplemental Digital Content is available in the text.